Development and validation of polymer-based porphyrin-incorporated reference materials for calibration of quantitative light-induced fluorescence device - Sang-Eun Park; Hong-Cheol Yoon; Elbert de Josselin de Jong; Kwang-Mahn Kim; Jae-Sung Kwon (Photodiagnosis and Photodynamic Therapy)
Background: This study aimed at developing and validating polymer-based reference materials with varying amounts of porphyrin to accurately assess and calibrate quantitative light-induced fluorescence (QLF) device. Methods: Reference materials with porphyrin concentrations ranging from 0 to 0.08 wt.% were prepared. The surface properties of the materials were analyzed via gloss and roughness measurements. Color analysis of the specimens was performed on black and white backgrounds with or without filters using a spectrophotometer. This approach revealed the correlations between fluorescence and color. The fluorescence emitted by the specimens was analyzed by measuring ΔR and ΔRmax values using a QLF-D Biluminator™. Results: The surface gloss and roughness of the reference materials were not affected by the porphyrin content (p > 0.005). Spectrophotometric measurements revealed significant color differences among most specimen groups depending on the background color and the presence of a filter. QLF-D imaging revealed significant differences in fluorescence (ΔR and ΔRmax) among all specimen groups regardless of the background. The fluorescence values observed on the black backgrounds were higher than those observed on the white backgrounds (p < 0.05). Conclusions: The developed polymer-based porphyrin-incorporated materials serve as reliable reference standards for accurate assessment and calibration of QLF devices. This study demonstrates the importance of background conditions in fluorescence detection and highlights the potential of these materials as standards for QLF device calibration.